FORMATION AND ASSESSMENT OF STUDENTS' INFORMATION COMPETENCIES IN EXTRA-CLASS WORK IN INFORMATION SCIENCE - Salgozha, И.Т.; Toishybek, Т.; Shekerbaeva, Ш.Н. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
The article addresses the timely topic of evaluating students' information competence in the context of modern educational informatization. Information competence is crucial for successful adaptation to a digital society and personal development. The study aimed to develop and implement a methodology to assess students' information competence, focusing on extracurricular activities in computer science. The research involved a literature analysis, creation and testing of original tests and questionnaires, and statistical data analysis. Results revealed various aspects of students' information competence, including skills in working with information, source reliability assessment, data analysis, and problem-solving. Relationships were found between information competence and factors like age, education, and technology use experience. The study emphasizes the need to integrate information competence into computer science curricula and extracurricular activities, offering a foundation for future educational strategies. Overall, the research contributes significantly to education and information competence, enhancing students' readiness for the challenges of the digital age.